BDNF/CREB signaling pathway contribution in depression pathogenesis: A survey on the non-pharmacological therapeutic opportunities for gut microbiota dysbiosis - Somaieh Matin; Masoomeh Dadkhah (Brain Research Bulletin, 2024)
Emerging evidence supports the gut microbiota and the brain communication in general health. This axis may affect behavior through modulating neurotransmission, and thereby involve in the pathogenesis and/or progression of different neuropsychiatric disorders such as depression. Brain-derived neurotrophic factor and cAMP response element-binding protein known as CREB/BDNF pathway plays have critical functions in the pathogenesis of depression as the same of mechanisms related to antidepressants. However, the putative causal significance of the CREB/BDNF signaling cascade in the gut-brain axis in depression remains unknown. Also interventions such as probiotics supplementation and exercise can influence microbiome also improve bidirectional communication of gut and brain. In this review we aim to explain the BDNF/CREB signaling pathway and gut microbiota dysfunction and then evaluate the potential role of probiotics, prebiotics, and exercise as a therapeutic target in the gut microbiota dysfunction induced depression. The current narrative review will specifically focus on the impact of exercise and diet on the intestinal microbiota component, as well as the effect that these therapies may have on the microbiota to alleviate depressive symptoms. Finally, we look at how BDNF/CREB signaling pathway may exert distinct effects on depression and gut microbiota dysfunction.